Comparison of clinical efficacy and safety of thermotherapy versus cryotherapy in treatment of skin warts: A randomized controlled trial. Issue 1 (30th October 2017) - Izadi Firouzabadi, Leila; Khamesipour, Ali; Ghandi, Narges; Hosseini, Hamed; Teymourpour, Amir; Firooz, Alireza
Abstract: The effect of thermotherapy in the treatment of skin warts in comparison to cryotherapy, as the standard conventional method, has remained uncertain. This study aimed to assess the clinical efficacy and safety of thermotherapy and cryotherapy in removing skin warts. This randomized controlled trial was conducted on 52 patients aged 18 years and over with ≤ 10 skin warts. The participants were randomly assigned into two groups to receive cryotherapy (every 2 to 3 weeks up to six sessions if required) or thermotherapy (one session). The patients in both groups were followed every 2 to 3 weeks for the first three months, and then three months after the last treatment session. The clearance rate was 79.2% in the thermotherapy group and 58.3% in the cryotherapy group with no significant difference ( p  = 0.212). The rate of scarring in the thermotherapy group was 20% ( p  = .018). A higher clearance rate was achieved in the thermotherapy group. However, this result was not statistically significant. There were some minimal post‐treatment complications. Patients needed only one session of thermotherapy. Due to the risk of scarring, we suggest thermotherapy only as a suitable treatment method for palmoplantar warts.